Policy process in Indonesia during COVID-19: a cross-sectoral policy perspective - Evi Satispi; Ma'mun Murod (Department of Government Studies Universitas Muhammadiyah Makassar, 2023)
This paper aims to examine the policy process for dealing with COVID-19 in Indonesia; in the last two years, the Indonesian government have taken various policy for dealing with COVID-19. Currently, this field still lacks in demonstration of cross-sectoral policy in Indonesia. This research uses qualitative explorative systematic analysis focusing on cross-sectoral policies taken by the government. This study found that government policies dealing with COVID-19 take a long time to implement owing to the cross-institutional policy process and being inactive. These policy decisions are impacted by the state's capacity to handle policy concurrently so that the government has long-term policy alternatives. Nonetheless, this policy decision will have a long-term influence on how Indonesia handles COVID-19. In the instance of Indonesia, this study reveals two policy options: substantive policy and procedural policy.